2022
DOI: 10.1186/s12885-022-09297-7
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative versus postoperative chemo-radiotherapy for locally advanced gastric cancer: a multicenter propensity score-matched analysis

Abstract: Background Peri-operative chemo-radiotherapyplayed important rolein locally advanced gastric cancer. Whether preoperative strategy can improve the long-term prognosis compared with postoperative treatment is unclear. The study purpose to compare oncologic outcomes in locally advanced gastric cancer patients treated with preoperative chemo-radiotherapy (pre-CRT) and postoperative chemo-radiotherapy (post-CRT). Methods From January 2009 to April 2019… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…There may be two mechanisms by which radiotherapy improves the survival of patients with radical gastrectomy. On one hand, preoperative radiotherapy can lower down tumor staging, make unresectable patients eligible for surgery, and improve the R0 resection rate [ 13 ]. On the other hand, radiotherapy helps to control micrometastasis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There may be two mechanisms by which radiotherapy improves the survival of patients with radical gastrectomy. On one hand, preoperative radiotherapy can lower down tumor staging, make unresectable patients eligible for surgery, and improve the R0 resection rate [ 13 ]. On the other hand, radiotherapy helps to control micrometastasis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…After PSM, the preoperative group had better OS and DFS, better treatment compliance, and similar surgical complications compared with the preoperative group [ 14 ]. Similarly, Li and colleagues also found that patients with stage T 3/4 and/or N positive gastric cancer treated with surgery and preoperative CRT had better efficacy and survival than patients treated with surgery and postoperative CRT [ 13 ]. These results are in dispute with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation